PENGARUH PENGGUNAAN METODE TUTOR SEBAYA TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN PAI DI SMP NEGERI 1 KECAMATAN PAYAKUMBUH - Bella Elfindra; Supriadi, Mustafa, Hamdi Abdul Karim (Jurnal Salome : Multidisipliner Keilmuan, 2023)
One factor that can influence learning motivation is learning methods. This research was motivated by a problem when the researcher made observations, where there were still some students who lacked enthusiasm for learning, did not listen to the teacher, and still had low motivation. The purpose of this study is to analyze the seventh grade PAI class at SMP Negeeri 1 in the Payakumbuh District to see how the peer tutoring method affected the students' enthusiasm to learn. Thinking about how little relevant and suitable procedures are used. By dividing a population into a control group and an experimental group, IM studies employ a quasi-experimental study design. The students in both classes will be given pre- and post-tests as part of this research. The research found that the Sig. (pvalue) = 0.026a 0.05 for the control class and experimental class indicated that Ho is rejected and H1 is accepted, respectively, in the hypothesis testing. The computations show that the implementation of the peer-guided learning technique affects the learning outcomes of seventh grade PAI students at SMP Negeri 1 Kecemaaten Payakumbuh.